2000
DOI: 10.6028/jres.105.033
|View full text |Cite
|
Sign up to set email alerts
|

Radiative calibration of heat-flux sensors at NIST: Facilities and techniques

Abstract: We present an overview of the National Institute of Standards and Technology high temperature blackbodies, both in operation and in development, suitable for heat-flux sensor calibration. Typical results of calibrations using the transfer technique in the 25 mm Variable-Temperature Blackbody are presented to demonstrate the long-term repeatability of the calibration technique. A comparative study of the absolute and transfer calibrations of a Gardon gage in a spherical blackbody with a cooled enclosure surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 4 publications
(4 reference statements)
2
16
0
Order By: Relevance
“…3000 K The majority of the requirements mentioned above for matching the properties of calibration light sources and shock pyrometry experiments can be easily satisfied when the measured temperatures do not exceed approximately 2300 K. Many commercially available, compact blackbody simulators operate below 1800 K. 12,13,41 Some experimental models were reported that operate up to 3300 K. [42][43][44] However, reasonably stable and well-characterized blackbodies operating above 3000 K are quite bulky and require water cooling and inert gas purging of window-covered hot cavities. 45,46 We found only two vendors of commercial blackbody simulators operating above 2300 K. 47,48 Each of these devices weighs approximately 182 kg and has a volume of 0.7-0.8 m 3 .…”
Section: Review Of Calibration Sources For Shock Temperature Pyromentioning
confidence: 99%
“…3000 K The majority of the requirements mentioned above for matching the properties of calibration light sources and shock pyrometry experiments can be easily satisfied when the measured temperatures do not exceed approximately 2300 K. Many commercially available, compact blackbody simulators operate below 1800 K. 12,13,41 Some experimental models were reported that operate up to 3300 K. [42][43][44] However, reasonably stable and well-characterized blackbodies operating above 3000 K are quite bulky and require water cooling and inert gas purging of window-covered hot cavities. 45,46 We found only two vendors of commercial blackbody simulators operating above 2300 K. 47,48 Each of these devices weighs approximately 182 kg and has a volume of 0.7-0.8 m 3 .…”
Section: Review Of Calibration Sources For Shock Temperature Pyromentioning
confidence: 99%
“…The blackbody can be heated up to 500 K with a DC power supply. The calibration is performed in vacuum, so that only radiative transfers occur between the blackbody and the HFM, satisfying thus the NIST (National Institute of Standard and Technology) procedure [19].…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The inferred heat flow had 10% uncertainty (for Q f = 12 W). This contrasts with estimates of 2% error for proprietary heat flux meters as measured at NIST using steady radiative heat flow [14] or 3% considering unsteady spray cooling [15]. …”
Section: Theoretical Backgroundmentioning
confidence: 58%